2023
DOI: 10.3389/fnins.2023.1174399
|View full text |Cite
|
Sign up to set email alerts
|

Improved HHT-microstate analysis of EEG in nicotine addicts

Abstract: BackgroundSubstance addiction is a chronic disease which causes great harm to modern society and individuals. At present, many studies have applied EEG analysis methods to the substance addiction detection and treatment. As a tool to describe the spatio-temporal dynamic characteristics of large-scale electrophysiological data, EEG microstate analysis has been widely used, which is an effective method to study the relationship between EEG electrodynamics and cognition or disease.MethodsTo study the difference o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…These findings extend previous studies on topographies of frequency-decomposed microstates (Musaeus et al, 2020; Férat et al, 2022; Terpou et al, 2022; Xiong et al, 2023). Férat et al (2022) and Terpou et al (2022) fitted broadband microstate maps directly to all other frequency bands, which might neglect distinct topographic configurations in a specific frequency band.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings extend previous studies on topographies of frequency-decomposed microstates (Musaeus et al, 2020; Férat et al, 2022; Terpou et al, 2022; Xiong et al, 2023). Férat et al (2022) and Terpou et al (2022) fitted broadband microstate maps directly to all other frequency bands, which might neglect distinct topographic configurations in a specific frequency band.…”
Section: Discussionsupporting
confidence: 90%
“…Musaeus and colleagues (2020) defined a four-cluster solution (k = 4) and reported different topographies across different EEG frequency bands. More recently, Xiong et al (2023) defined the optimal number of clusters based on GEV and cross-validation criterion (Koenig et al, 2014). They reported that this number varies with frequency bands for task-state EEG, which enabled participants to focus on the smoking-related or paired neutral pictures.…”
Section: Discussionmentioning
confidence: 99%